Inflammatory activity evaluation in patients with axial spondyloarthritis using MRI relaxometry and mucosal-associated invariant T cells - Yang, Shengsheng; Zheng, Yonghong; Chen, Xianyuan; Lin, Mingui; Dai, Xiaomin; Gao, Fei; Chen, Huangjing; Ma, Mingping; Yu, Shun (Frontiers in Immunology, 2024)
Currently, there is a lack of an objective quantitative measure to comprehensively evaluate the inflammatory activity of axSpA, which poses certain challenges in accurately assessing the disease activity.To explore the value of combined-parameter models of sacroiliac joints (SIJs) MRI relaxometry and peripheral blood Mucosal-associated invariant T (MAIT) cells in evaluating the inflammatory activity of axial spondyloarthritis (axSpA).METHODS. This retrospective clinical study included 88 axSpA patients (median age 31.0 (22.0, 41.8) years, 21.6% females) and 20 controls (median age 28.0 (20.5, 49.5) years, 40.0% females). The axSpA group was classified into active subgroup (n=50) and inactive subgroup (n=38) based on ASDAS-CRP. All participants underwent SIJs MRI examination including T1 and T2* mapping, and peripheral blood flow cytometry analysis of MAIT cells (defined as CD3 + Vα7.2 + CD161 + ) and their activation markers (CD69). The T1 and T2* values, as were the percentages of MAIT cells and CD69 + MAIT cells were compared between different groups. Combinedparameter models were established using logistic regression, and ROC curves were employed to evaluate the diagnostic efficacy.The T1 values of SIJs and %CD69 + MAIT cells in the axSpA group and its subgroup were higher than the control group (p<0.05), while %MAIT cells were lower than the control group (p<0.05). The T1 values and %CD69 + MAIT cells correlated positively, while %MAIT cells correlated negatively, with the ASDAS- CRP (r=0.555, 0.524, p<0.001). Between the control and axSpA groups, and between the inactive and active subgroups, the combined-parameter model T1 mapping+%CD69 + MAIT cells has the best efficacy (AUC=0.959, 0.879, sensibility=88.6, 70%, specificity=95.0, 94.7%, respectively).The combined-parameter model T1 mapping+%CD69 + MAIT cells allows a more accurate evaluation of the level of inflammatory activity.